2022
DOI: 10.1039/d1cc05022b
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene metallopolymers of intrinsic microporosity (MPIMs)

Abstract: Ferrocene-containing polymers can simultaneously possess porosity, solubility, and intrachain electronic communication.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…As a result, ferrocene-based metallopolymers are a distinctive class of functional materials that have gained much attention in recent years. [46][47][48][49][50] The possibility to tune the properties of ferrocene-based polymers and macromolecules relies on the redox activity of ferrocene, since this organometallic molecule undergoes fast one-electron oxidation to the positively charged ferrocenium form [Fe(η 5 -C 5 H 5 ) 2 ] + . By switching the redox state (Fe II /Fe III ) of the multiple ferrocenyl units (separately, or in a cooperative fashion) the charge, polarity, color, and hydrophilicity of the molecules may be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, ferrocene-based metallopolymers are a distinctive class of functional materials that have gained much attention in recent years. [46][47][48][49][50] The possibility to tune the properties of ferrocene-based polymers and macromolecules relies on the redox activity of ferrocene, since this organometallic molecule undergoes fast one-electron oxidation to the positively charged ferrocenium form [Fe(η 5 -C 5 H 5 ) 2 ] + . By switching the redox state (Fe II /Fe III ) of the multiple ferrocenyl units (separately, or in a cooperative fashion) the charge, polarity, color, and hydrophilicity of the molecules may be controlled.…”
Section: Introductionmentioning
confidence: 99%
“…12 Polymers of intrinsic microporosity are known to enhance a broad array of sustainable energy technologies. 13,14 Although there is a general understanding of how each of these types of materials function independently, until recently, 15 few studies have investigated how the properties of all three would interact in a single material. For instance, incorporating metal centers into conjugated organic polymers has been shown to increase the conductivity of the material.…”
mentioning
confidence: 99%
“…The recent synthesis and characterization of Fc metallopolymers of intrinsic microporosity (MPIMs) has shown that it may be possible to combine the optoelectronic properties of conjugated organic polymers, the high conductance of Fc in molecular junctions, and the high surface area of intrinsically microporous materials within a single, soluble non-network polymer. 15 One area in which conjugated MPIMs may have a significant impact is in BHJ solar cells.…”
mentioning
confidence: 99%